Exploratory Study on the Psychosocial Impact of the Coronavirus Disease (COVID-19) Outbreak on Asian Students Living in Turkey - Gunda, Abdulhamid (İstanbul Sabahattin Zaim Üniversitesi, 2020)
The Coronavirus (COVID-19) pandemic has caused widespread fear and stress around the world. People’s reactions to the crisis have aggravated social problems such as social discrimination and xenophobia. The most vulnerable groups who have felt the immediate impact of outbreak-related discrimination include international students who originated from different countries in Asia. In this connection, the study aimed to explore the immediate psychosocial impact of the COVID-19 outbreak on Asian students in Turkey. Significantly, this paper aimed to help gather valuable information in mapping psychosocial support guidelines for people affected by the pandemic. The respondents of the study are bona fide students at different universities across Turkey. The study is cross-sectional and utilized a semi-structured questionnaire to collect the necessary data. The questions, which are researched and based on literature review, were sent to different organizations, associations, and/or groups of international students from Asia via a google form. Generally, the questionnaire included the socio-demographic characteristics of the participants, COVID-19 impact, related specific psychosocial experiences, and the preventive measures taken during the pandemic. The Statistical Package for Social Sciences (SPSS) was utilized for data analyses. Chi-square test or Fisher’s exact was applied to determine the variables that are associated with self-reported COVID-19 impact.Furthermore, the work aimed for results that are beneficial to the tailoring of social support to the vulnerable groups during the outbreak through increasing public awareness and facilitation of more inclusive policies. It specifically looked for valuable results that will seek to help health policymakers and service providers to develop inclusive and effective interventions towards international students during disease outbreak such as the COVID-19.
İZÜ Sosyal Bilimler Lisansüstü Öğrenci Kongresi, 6-7 Haziran 2020 (ONLINE)
Keywords: Asian students; Psychosocial; Discrimination; Coronavirus disease